A indicação geográfica sob a perspectiva dos produtores de queijo de coalho de Nossa Senhora da Glória-SE - Fraga, Érica Emília Almeida (2016)
The consumer market has incorporated more strongly an old practice of assigning certain products assessments of values that go beyond cost effective. This rating system is based on the certification of quality production, differential of the finished product and the properties that connect their products to an own set of knowledge of a community located geographically. This certification is called the Geographical Indication (GI), which can be in the form of Designation of Origin (DO) or Indication of Origin (IP, in Portuguese). In this sense, this study aimed to analyze the curd cheese type of Nossa Senhora da Glória, Sergipe state, Brazil, considering the conditions of production and the perception of producers in order to check if they meet the basic requirements for obtaining a GI. The question is whether the rennet-curd cheese artisanal shops of the small town studied are prepared to obtain the IG, the National Institute of Industrial Property (INPI, in Portuguese). The research is characterized such as literature, field and case study, based on quantitative and qualitative analysis. It was applied a non-probability sampling for convenience, using the structured questionnaire and interview as tools and applied to the sample of 24 curd cheese type artisanal shops. Quantitative data were treated under the descriptive statistical method. The results showed that the artisanal shops on their part are managed by men (87.5%) and 91% with low education. It also showed that the artisanal shops mostly (95.84%) are not part of any representative body. The owners (95.84%) showed that the cheese know-how has been transmitted from generation to generation. 70% intended production to intermediaries and in foreign markets, mostly in the state of Paraíba. The results show that 100% of artisanal shops are geographically located in the countryside and that these (83.33%) are unaware of the standards and health standards set by the industry. On Good Manufacturing Practices (GMP's), 98% said they do not know and the structure of the little factory does not meet the standards and sanitary standards. All owners have never heard about the IG, but are interested in being part of the recognition and GI registration process.